Ibrutinib- and bortezomib-extended R-CHOP induction in elderly higher-risk patients newly diagnosed with diffuse large B-cell lymphoma – first analysis of toxicity and efficacy signals. Issue 1 (2nd January 2022) - Denker, Sophy; Bittner, Aitomi; Frick, Mareike; Kase, Julia; Hoffmann, Jörg; Trenker, Corinna; Keller, Ulrich; Bogner, Christian; Hüttmann, Andreas; Dürig, Jan; Janz, Martin; Mathas, Stephan; et al.
Abstract: Diffuse large-cell B-cell lymphoma (DLBCL) is the most common lymphoid malignancy. About 30–40% of the patients will not be cured by standard Rituximab (R)-CHOP-like immune-chemotherapy, and many of them experience relapse and eventually succumb to their disease. Enhancing first-line efficacy in patients at higher risk, among them many elderly, is key to improve long-term outcomes. Numerous attempts to combine R-CHOP with targeted agents failed in large randomized phase III trials. The addition of Ibrutinib enhanced survival in younger patients, but increased toxicity across all age groups, especially in the elderly. Older DLBCL patients impose particular challenges, since they often present with more advanced disease, and exhibit treatment-relevant comorbidities. ImbruVeRCHOP trial aims at identifying patients who need that benefit from rationally augmented first-line regimens without experiencing overt toxicity and detecting their molecular signatures of response. This first analysis presents encouraging feasibility, safety, and preliminary response data in elderly high-risk DLBCL patients.